PROPERTY RELATIONS IN THE INVESTMENT AND CONSTRUKTION COMPLEX - A. Kozlovskiy; A. Pepoyan (Вестник университета)
The problem of the relationship between the concepts of property. The historical aspects of the formation of the property category in Russia are indicated is considered. The economic and legal aspects of the concept of property are considered. The main forms of ownership and their shares in the total number of construction companies on the Russian market are described. The mechanism of profit distribution in the investment and construction complex in accordance with the share of ownership of each participant in the construction process is described. The importance of investment risks in the formation of construction projects is reflected, as well as the importance of large vertically integrated structures in the form of investment and construction companies that allow the entire investment and construction cycle to be closed within the same company.